MBRS-72. MiR-212 FUNCTIONS AS A TUMOR SUPPRESSOR GENE IN GROUP 3 MEDULLOBLASTOMA VIA TARGETING NUCLEAR FACTOR I/B (NFIB). (4th December 2020) - Perumal, Naveenkumar; Kanchan, Ranjana; Atri, Pranita; Venkata, Ramakanth; Thapa, Ishwor; Nasser, Mohd; Batra, Surinder; Mahapatra, Sidharth
Abstract: Medulloblastoma (MB), the most frequent malignant pediatric brain tumor is divided into four primary subgroups, i.e. wingless-type (WNT), sonic hedgehog (SHH), group 3, and group 4. Haploinsufficiency of chromosome 17p13.3 and c-myc amplification distinguish high-risk group 3 tumors and are associated with rapid recurrence and early mortality. We sought to identify the role of miR-212, which resides on chromosome 17p13.3, in the pathophysiology of group 3 medulloblastoma. RNA expression analyses revealed dramatically reduced levels of miR-212 in group 3 tumors and cell lines mainly through epigenetic silencing via histone modification (deacetylation). Restoring in vitro expression reduced tumor cell proliferation with decreased p-AKT and p-ERK levels, colony formation, migration and invasion in group 3 MB. Interestingly, a shift in differential c-myc phosphorylation (from serine-62 to threonine-58) was noted, resulting in reduced total c-myc levels, concurrent with elevated cellular apoptosis. In turn, pro-apoptotic binding partners of c-myc, i.e. Bin-1 and P19 ARF, were upregulated in these cells. A dual luciferase assay confirmed direct targeting of miR-212 to NFIB, a nuclear transcription factor implicated in metastasis and recurrence. Concurrently, increased expression of NFIB was confirmed in group 3 MB tumors with poor survival in high NFIB-expressing patients. Transient NFIB silencing in vitro reduced tumor cell proliferation, migration and invasion, and medullosphere formation along with a reduction in stem cell markers (Nanog, Oct4, Sox2, CD133) and the multi-drug resistance maker, ABCG2. Taken together, these results substantiate the tumor suppressive role of miR-212 in group 3 medulloblastomas and provide a potential new therapeutic target, NFIB.